Do u have a diagram to show
Answer:
b, d, and E
Step-by-step explanation:
when you multiplicate all, is the same results
ANSWER
![\boxed {m \ne0}](https://tex.z-dn.net/?f=%20%5Cboxed%20%7Bm%20%5Cne0%7D)
EXPLANATION
The given function is
![f(x) = mx + b](https://tex.z-dn.net/?f=f%28x%29%20%3D%20mx%20%2B%20b)
We need to find the inverse of this function,
Let
![y= mx + b](https://tex.z-dn.net/?f=%20y%3D%20mx%20%2B%20b)
We interchange x an y to obtain,
![x = my + b](https://tex.z-dn.net/?f=x%20%3D%20my%20%2B%20b)
We solve for y now to obtain,
![x - b = my](https://tex.z-dn.net/?f=x%20-%20b%20%3D%20my)
We divide through by m to get,
![\frac{x - b}{m} = y](https://tex.z-dn.net/?f=%20%5Cfrac%7Bx%20-%20b%7D%7Bm%7D%20%20%3D%20y)
Hence the inverse function is ,
![{f}^{ - 1} (x) = \frac{x - b}{m}](https://tex.z-dn.net/?f=%20%7Bf%7D%5E%7B%20-%201%7D%20%28x%29%20%3D%20%20%5Cfrac%7Bx%20-%20b%7D%7Bm%7D%20)
For this inverse to exist, the denominator must not be equal to zero,
Thus
![m \ne0](https://tex.z-dn.net/?f=m%20%5Cne0)
The correct answer is A.